A positive electrode material, a preparation method and application thereof
Patent Information
- Application Number
- CN202611243522.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-17
- Publication Date
- 2026-10-27
AI Technical Summary
然而,现有技术中的玻璃其热膨胀系数、软化点及化学组成并不适配于在纳米/亚微米尺度对磷酸锰铁锂颗粒进行包覆
[0021]本发明还提供一种正极片,其包含如前所述的正极材料。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery technology, and in particular to a cathode material, its preparation method, and its application. Background Technology
[0002] Lithium manganese iron phosphate (LMFP) combines the high safety of lithium iron phosphate (LFP) with the high voltage platform of lithium manganese phosphate (LMP) (approximately 4.1V vs. Li). + MnO2 (Li) is considered one of the ideal cathode materials for next-generation high-energy-density, low-cost lithium-ion batteries. However, its practical application is constrained by two key bottlenecks: (1) its inherent low electronic conductivity and lithium-ion diffusion rate lead to poor rate performance; (2) during cycling, due to the low electron conductivity and lithium-ion diffusion rate, the material's rate performance is poor. 3+ The Jahn-Teller effect exacerbates the disproportionation reaction, generating Mn. 2+ Dissolution leads to the loss of active substances and structural collapse, resulting in a sharp decline in cycle stability.
[0003] To address the aforementioned issues, surface coating is one of the most effective strategies for modifying lithium manganese iron phosphate. Carbon coating can effectively improve electronic conductivity, but its effect on inhibiting manganese dissolution and improving lithium-ion interfacial transport is limited, and excessively thick carbon layers can reduce volumetric energy density. Organic / polymer coatings, such as silane compounds or small organic molecules containing specific functional groups, can uniformly modify the surface through chemical bonding, alleviating HF corrosion, but their intrinsic electronic / ionic conductivity is low and their thermal stability is poor. Fast ion conductor coatings, such as lithium zirconium phosphate (LZPO) and lithium lanthanum zirconium oxide (LLZO), can promote lithium-ion transport at the interface and reduce impedance. However, a single inorganic ion conductor layer is often difficult to form a continuous, dense, and strongly adherent coating layer, resulting in insufficient physical isolation from the electrolyte.
[0004] Recently, some studies have introduced glass phases into cathode material coatings. For example, CN120978046A discloses a transition metal layered oxide cathode material for lithium-ion batteries, its preparation method, the cathode material, and a lithium-ion battery. Due to the material's high-temperature resistance, it is directly coated onto the surface of the layered oxide using a heat treatment method. However, the thermal expansion coefficient, softening point, and chemical composition of existing glasses are not suitable for coating lithium manganese iron phosphate particles at the nano / submicron scale. These glasses typically require extremely high melting temperatures, which can damage the structure of lithium manganese iron phosphate, and their composition may contain a large amount of alkali metals, posing a risk of migration within the battery and affecting long-term stability. Summary of the Invention
[0005] Based on this, the purpose of this invention is to provide a cathode material, its preparation method, and its application. By combining glass additives with lithium fast ion conductors, a synergistic coating structure of glass bonding phase + ion-conducting phase is constructed on the surface of lithium manganese iron phosphate. While achieving physical isolation, the diffusion barrier and interfacial impedance of lithium ions on the particle surface are significantly reduced, thereby simultaneously improving the cycle stability and rate performance of lithium manganese iron phosphate material.
[0006] To achieve the above objectives, the present invention adopts the following technical solution: The present invention provides a cathode material comprising a core and a coating layer covering the core, wherein the core comprises lithium manganese iron phosphate and the coating layer comprises an interwoven glass phase and a fast lithium-ion conductor.
[0007] This invention constructs a synergistic coating structure of glass binder and ion-conducting phase on the surface of lithium manganese iron phosphate by combining glass additives with fast lithium-ion conductors. This achieves physical isolation while significantly reducing the diffusion barrier and interfacial impedance of lithium ions on the particle surface, thereby simultaneously improving the cycle stability and rate performance of the lithium manganese iron phosphate material. Furthermore, the fast ion conductor in the coating layer provides a rapid lithium-ion transport channel, improving the material's electrical properties. The dense glass phase effectively isolates the electrolyte from direct contact with the active material, significantly suppressing manganese / iron dissolution (manganese dissolution is extremely low); the stable glass network and LZPO crystals enhance the structural integrity of the coating layer, preventing breakage during cycling.
[0008] As a further improvement to the above-mentioned solution of the present invention, the fast lithium-ion conductor is one of lithium zirconium phosphate, lithium titanium aluminum phosphate, lithium lanthanum zirconium oxide, and lithium germanium aluminum phosphate.
[0009] As a further improvement to the above-described scheme of the present invention, the thickness of the coating layer is 5~50 nm.
[0010] The present invention also provides a method for preparing the cathode material as described above, which includes the following steps: mixing glass additives, lithium fast ion conductor precursors and lithium manganese iron phosphate powder, and heat treating to obtain the cathode material.
[0011] During the heat treatment process, the glass additive melts and spreads, forming a continuous and dense composite coating layer on the surface of the lithium manganese iron phosphate particles together with some of the fast ion conductors generated by in-situ reactions. Furthermore, the glass phase acts as a binder, fixing the fast ion conductor particles to the surface of the lithium manganese iron phosphate matrix and filling gaps, together constructing a low-impedance ion-conducting interface. This provides a rapid lithium-ion transport channel for the fast ion conductors in the coating layer, improving the electrical properties of the material.
[0012] As a further improvement to the above-described scheme of the present invention, the glass additive comprises the following components in molar percentage: 35%~55% B2O3, 15%~30% Li2O, 5%~15% SiO2, 3%~10% Al2O3, 2%~8% ZrO2, and 1%~5% P2O5.
[0013] This glass additive can melt and flow at relatively low heat treatment temperatures, forming a continuous, dense, and chemically stable amorphous coating layer. It physically blocks the corrosion of HF in the electrolyte, fundamentally isolating the electrolyte from direct contact with the active material and effectively inhibiting the dissolution of manganese ions. B2O3 significantly lowers the melting temperature and softening point of the glass, allowing it to melt below the sintering temperature of lithium manganese iron phosphate, forming a uniform coating. Simultaneously, the introduction of B2O3 enhances the density of the glass network, improving its barrier properties against the electrolyte. Li2O provides mobile Li... + Lithium-ion conductivity is inherent in the glass phase. SiO2, as an auxiliary network former, enhances the chemical stability and mechanical strength of the glass structure. However, excessive SiO2 content can lead to a sharp increase in glass melting temperature, which is detrimental to low-temperature coating processes. Al2O3, as a network intermediate, can enter the glass network, improving the glass's chemical durability, particularly its resistance to HF corrosion in the electrolyte. ZrO2 promotes the controlled precipitation of microcrystals in the glass, improving its moisture resistance and mechanical strength. Furthermore, ZrO2 is one of the precursors for synthesizing subsequent composite fast-ion conductors (such as lithium zirconium phosphate). P2O5 may share structural similarities with the phosphate groups on the surface of lithium manganese iron phosphate, which helps improve the interfacial compatibility and bonding strength between the coating layer and the substrate.
[0014] The glass additives of this invention are mainly composed of elements such as Li, B, Si, Al, Zr, and P, which avoids the introduction of easily migrating alkali metals such as Na and K, ensuring structural and chemical stability during long-term electrochemical cycling. The overall performance is significantly better than that of materials coated with a single carbon or a single ion conductor.
[0015] As a further improvement of the above-mentioned solution of the present invention, the preparation method of the glass additive is as follows: weigh each component raw material according to the proportion, mix them, melt them at 1000~1250℃ for 1-3 hours, quench, dry and ball mill them to obtain a glass additive with a particle size D50 of 0.3~1.0μm; each component raw material is an oxide, carbonate, nitrate or hydroxide.
[0016] As a further improvement to the above-mentioned solution of the present invention, the lithium fast ion conductor is lithium zirconium phosphate, and the lithium fast ion conductor precursor is a solution or powder containing a lithium source, a zirconium source and a phosphorus source.
[0017] As a further improvement to the above-mentioned scheme of the present invention, the sum of the mass of the glass additive and the lithium fast ion conductor accounts for 0.5% to 4.0% of the mass of lithium manganese iron phosphate.
[0018] As a further improvement to the above-mentioned solution of the present invention, the mass ratio of the glass additive to the lithium fast ion conductor is (1:4) to (4:1).
[0019] As a further improvement to the above-mentioned solution of the present invention, the mixing is carried out by wet ball milling or solvent dispersion.
[0020] As a further improvement to the above-mentioned solution of the present invention, the heat treatment is carried out in an inert atmosphere or a weakly reducing atmosphere, with the temperature increased to 600-800°C at a rate of 1-5°C / min and held for 2-8 hours.
[0021] The present invention also provides a positive electrode sheet comprising the positive electrode material as described above.
[0022] The present invention also provides a lithium battery comprising the positive electrode as described above. The lithium battery of the present invention retains ≥89% capacity after 500 cycles at 1C rate. Detailed Implementation
[0023] To facilitate understanding of the present invention, a more comprehensive description will be given below with reference to specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a more thorough and complete understanding of the disclosure of the present invention.
[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention.
[0025] As described in the background section of this application, it is currently difficult to form a continuous, dense, and strongly adherent coating layer by coating lithium manganese iron phosphate with a single fast-ion conductor, resulting in insufficient physical isolation effect on the electrolyte. Furthermore, the current method of introducing a glass phase into the cathode material for coating typically requires extremely high melting temperatures, which can damage the structure of lithium manganese iron phosphate. To address this problem, this application provides a cathode material, its preparation method, and its application.
[0026] In a first typical embodiment of this application, a cathode material is provided, comprising a core and a coating layer covering the core. The core comprises lithium manganese iron phosphate, and the coating layer comprises an interwoven glass phase and a fast lithium-ion conductor.
[0027] By combining glass additives with fast lithium-ion conductors, a synergistic coating structure of glass binder phase + ion-conducting phase is constructed on the surface of lithium manganese iron phosphate. This achieves physical isolation while significantly reducing the diffusion barrier and interfacial impedance of lithium ions on the particle surface, thereby simultaneously improving the cycle stability and rate performance of lithium manganese iron phosphate materials. Furthermore, the fast ion conductor in the coating layer provides a rapid lithium-ion transport channel, improving the electrical properties of the material.
[0028] In another embodiment, the fast lithium-ion conductor is one of lithium zirconium phosphate, lithium titanium aluminum phosphate, lithium lanthanum zirconium oxide, and lithium germanium aluminum phosphate. Lithium zirconium phosphate is preferred. The thickness of the coating layer is 5~50 nm.
[0029] In a second typical embodiment of this application, a method for preparing a cathode material is provided, which includes the following steps: mixing glass additives, lithium fast ion conductor precursors and lithium manganese iron phosphate powder, and heat-treating to obtain the cathode material.
[0030] During the heat treatment process, the glass additive melts and spreads, forming a continuous and dense composite coating layer on the surface of the lithium manganese iron phosphate particles together with some of the fast ion conductors generated by in-situ reactions. Furthermore, the glass phase acts as a binder, fixing the fast ion conductor particles to the surface of the lithium manganese iron phosphate matrix and filling gaps, together constructing a low-impedance ion-conducting interface. This provides a rapid lithium-ion transport channel for the fast ion conductors in the coating layer, improving the electrical properties of the material.
[0031] In another embodiment, the glass additive comprises the following components by molar percentage: 35%~55% B2O3, 15%~30% Li2O, 5%~15% SiO2, 3%~10% Al2O3, 2%~8% ZrO2, and 1%~5% P2O5. The glass additive is prepared by weighing the raw materials according to the specified proportions, mixing them, melting them at 1000~1250℃ for 1-3 hours, quenching, drying, and ball milling to obtain a glass additive with a particle size D50 of 0.3~1.0 μm; the raw materials are oxides, carbonates, nitrates, or hydroxides.
[0032] This glass additive can melt and flow at relatively low heat treatment temperatures, forming a continuous, dense, and chemically stable amorphous coating layer. It physically blocks the corrosion of HF in the electrolyte, fundamentally isolating the electrolyte from direct contact with the active material and effectively inhibiting the dissolution of manganese ions. B2O3 significantly lowers the melting temperature and softening point of the glass, allowing it to melt below the sintering temperature of lithium manganese iron phosphate, forming a uniform coating. Simultaneously, the introduction of B2O3 enhances the density of the glass network, improving its barrier properties against the electrolyte. Li2O provides mobile Li... +The glass phase is endowed with intrinsic lithium-ion conductivity. SiO2, as an auxiliary network former, enhances the chemical stability and mechanical strength of the glass structure. Excessive SiO2 content leads to a sharp increase in glass melting temperature, which is detrimental to low-temperature coating processes. Al2O3, as a network intermediate, can enter the glass network, improving the glass's chemical durability, especially its resistance to HF corrosion in the electrolyte. ZrO2 promotes the controlled precipitation of microcrystals in the glass, improving its moisture resistance and mechanical strength. Furthermore, ZrO2 is one of the precursors for synthesizing subsequent composite fast ion conductors (such as lithium zirconium phosphate). P2O5 may have structural similarities to the phosphate groups on the surface of lithium manganese iron phosphate, which helps improve the interfacial compatibility and bonding strength between the coating layer and the substrate. The glass additives of this invention are mainly composed of elements such as Li, B, Si, Al, Zr, and P, avoiding the introduction of easily migrating alkali metals such as Na and K, ensuring structural and chemical stability during long-term electrochemical cycling. The overall performance is significantly superior to materials coated with single carbon or single ion conductors.
[0033] In some embodiments, the lithium fast-ion conductor is lithium zirconium phosphate, and the lithium fast-ion conductor precursor is a solution or powder containing a lithium source, a zirconium source, and a phosphorus source. The sum of the mass of the glass additive and the lithium fast-ion conductor accounts for 0.5% to 4.0% of the mass of lithium manganese iron phosphate. The mass ratio of the glass additive to the lithium fast-ion conductor is (1:4) to (4:1). Mixing is performed by wet ball milling or solvent dispersion. Heat treatment is carried out in an inert or weakly reducing atmosphere, heating to 600 to 800°C at a rate of 1 to 5°C / min and holding at that temperature for 2 to 8 hours.
[0034] In a third typical embodiment of this application, a positive electrode sheet is provided, which comprises the positive electrode material as described above.
[0035] In a fourth typical embodiment of this application, a lithium battery is provided, comprising the positive electrode as described above. The lithium battery retains ≥89% capacity after 500 cycles at 1C rate.
[0036] The beneficial effects of this application will be further illustrated below with reference to embodiments and comparative examples.
[0037] Example 1 This embodiment proposes a cathode material, the preparation method of which is as follows: Preparation of glass additive: Based on the molar percentage composition of 50% B₂O₃, 23% Li₂O, 10% SiO₂, 6% Al₂O₃, 7% ZrO₂, and 4% P₂O₅, H₃BO₃, Li₂CO₃, SiO₂, Al(OH)₃, ZrO₂, and P₂O₅ were weighed out and thoroughly mixed in a ball mill. The mixture was then placed in an alumina crucible and placed in a box furnace. The temperature was increased to 1150℃ at 5℃ / min under air atmosphere and held for 2 hours to ensure complete melting and homogenization of the glass. Subsequently, the molten glass was rapidly poured into deionized water for quenching. The resulting glass slag was removed and dried at 120℃ for 12 hours. Finally, the dried glass block was placed in a planetary ball mill and ball-milled for 6 hours using ethanol as the medium. After drying, a glass additive powder with a D50 of approximately 0.4 μm was obtained.
[0038] Preparation of cathode material: Following the theoretical production of 1.5 g of LZPO, LiNO3, ZrO(NO3)2·xH2O, and NH4H2PO4 were dissolved in 20 mL of deionized water to obtain a lithium fast-ion conductor precursor solution; 100 g of LMFP matrix powder (commercial lithium manganese iron phosphate LiMn) was added... 0.6 Fe 0.4 0.75 g of glass additive powder (PO4, D50 = 1.5 μm) was added to a lithium fast ion conductor precursor solution and mixed. The mixture was then placed in a planetary ball mill jar, and 200 mL of anhydrous ethanol and an appropriate amount of zirconium oxide balls were added. The mixture was ball-milled at 300 rpm for 4 hours to ensure uniform dispersion and adhesion of the additive to the LMFP matrix surface. The slurry was filtered and dried. The dried powder was placed in a tube furnace and heated to 720°C at 3°C / min under an argon atmosphere, held at that temperature for 5 hours, and then cooled with the furnace. During the heat treatment, the glass additive melted, and simultaneously, lithium zirconium phosphate was generated in situ on the LMFP matrix surface, ultimately forming a coating layer on the LMFP particle surface composed of an interwoven glass phase and nanocrystalline lithium fast ion conductor.
[0039] Example 2 The difference between this embodiment and Embodiment 1 is that in this embodiment, the amount of glass additive powder added in the step of preparing the cathode material is 0.9g.
[0040] Example 3 The difference between this embodiment and Embodiment 1 is that in this embodiment, the amount of glass additive powder added is 1.05g in the step of preparing the cathode material.
[0041] Example 4 The difference between this embodiment and Example 1 is that in the step of preparing the glass additive in this embodiment, the components are composed of 45% B2O3, 25% Li2O, 10% SiO2, 8% Al2O3, 8% ZrO2, and 4% P2O5, and H3BO3, Li2CO3, SiO2, Al(OH)3, ZrO2, and P2O5 are weighed respectively.
[0042] Example 5 The difference between this embodiment and Embodiment 1 is that in this embodiment, the amount of glass additive powder added in the step of preparing the cathode material is 1.5g.
[0043] Example 6 The difference between this embodiment and Embodiment 1 is that in this embodiment, the amount of glass additive powder added in the step of preparing the cathode material is 2.0g.
[0044] Comparative Example 1 This comparative example directly uses commercially available lithium manganese iron phosphate (LiMn). 0.6 Fe 0.4 PO4, D50 = 1.5 μm.
[0045] Comparative Example 2 The difference between this comparative example and Example 1 is that the specific steps for preparing the cathode material in this comparative example are as follows: 100g of LMFP matrix powder (commercial lithium manganese iron phosphate LiMn) is added to the cathode material. 0.6 Fe 0.4 0.75 g of PO4 (D50 = 1.5 μm) glass additive powder was mixed and placed in a planetary ball mill jar. 200 mL of anhydrous ethanol and an appropriate amount of zirconia balls were added, and the mixture was ball-milled at 300 rpm for 4 hours to ensure uniform dispersion and adhesion of the additive to the LMFP matrix surface. The slurry was filtered and dried. The dried powder was placed in a tube furnace and heated to 720°C at 3°C / min under an argon atmosphere, held at that temperature for 5 hours, and then cooled with the furnace. During the heat treatment, the glass additive melted, ultimately forming a coating layer on the surface of the LMFP particles.
[0046] Comparative Example 3 This comparative example presents a cathode material, the preparation method of which is as follows: To theoretically generate 1.5 g of LZPO, LiNO3, ZrO(NO3)2·xH2O, and NH4H2PO4 were dissolved in 20 mL of deionized water to obtain a lithium fast ion conductor precursor solution; 100 g of LMFP matrix powder (commercial lithium manganese iron phosphate LiMn) was then added. 0.6 Fe 0.4Lithium zirconium phosphate (P4, D50 = 1.5 μm) was added to a lithium fast-ion conductor precursor solution and mixed. The mixture was then placed in a planetary ball mill jar, and 200 mL of anhydrous ethanol and an appropriate amount of zirconium oxide balls were added. The mixture was ball-milled at 300 rpm for 4 hours to ensure uniform dispersion and adhesion of the additive to the LMFP matrix surface. The slurry was filtered and dried. The dried powder was placed in a tube furnace and heated to 720°C at a rate of 3°C / min under an argon atmosphere, held at that temperature for 5 hours, and then cooled with the furnace. During the heat treatment process, lithium zirconium phosphate was generated in situ on the LMFP matrix surface, ultimately forming a coating layer on the LMFP particle surface.
[0047] Test case The lithium manganese iron phosphate cathode materials prepared in Examples 1-6 and Comparative Examples 1-3 were used to fabricate coin cells. The cathode slurry was prepared with NMP as solvent according to the mass ratio of active material, conductive carbon black, and PVDF binder of 90:5:5. The slurry was coated on aluminum foil current collector, dried, rolled, and stamped to obtain a circular cathode sheet. CR2032 coin cells were assembled in an argon glove box with water and oxygen content ≤0.1 ppm using lithium metal sheet as negative electrode, polypropylene microporous membrane as separator, and 1 mol / L LiPF6 / (EC-DEC) as electrolyte.
[0048] After the battery was immersed in a 25℃ environment for 12 h, its electrochemical performance was tested, with a voltage test window of 2.5~4.5 V. The specific capacity of the material during the first charge-discharge cycle at 0.1 C, the discharge performance at 1C rate, and the stability of 1C-500 cycles at room temperature were tested sequentially. The test results are shown in Table 1 below.
[0049] Table 1 Performance Test Results
[0050] As can be seen from the results in Table 1: Examples 1-6 of this invention employ LMFP materials co-coated with glass additives and LZPO. After 500 cycles at 1C, the capacity retention was significantly higher than that of the uncoated sample (Comparative Example 1, 78.6%), the glass-coated sample (Comparative Example 2, 83.1%), and the LZPO-coated sample (Comparative Example 3, 81.6%). This is attributed to the superior physical and chemical protective effects of the composite coating: the dense glass phase effectively isolates the electrolyte from direct contact with the active material, significantly inhibiting manganese / iron dissolution (manganese dissolution is extremely low); the stable glass network and LZPO crystals enhance the structural integrity of the coating, preventing cracking during cycling.
[0051] The glass additive and lithium fast ion conductor composite coating strategy provided by this invention comprehensively solves key problems such as low ionic conductivity, multiple interfacial side reactions and transition metal dissolution of LMFP materials by constructing a glass-ion conductor composite layer with excellent chemical stability, high ionic conductivity and strong mechanical strength on the surface of LMFP. It achieves significant effects in terms of high capacity, high rate capability, long cycle life and high temperature storage stability.
[0052] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0053] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.
Claims
1. A positive electrode material, characterized in that, It includes a core and a coating layer covering the core. The core includes lithium manganese iron phosphate, and the coating layer includes an interwoven glass phase and a fast lithium-ion conductor.
2. The lithium iron phosphate cathode material according to claim 1, characterized in that, The lithium fast ion conductor is one of lithium zirconium phosphate, lithium titanium aluminum phosphate, lithium lanthanum zirconium oxide, and lithium germanium aluminum phosphate.
3. The lithium iron phosphate cathode material according to claim 1, characterized in that, The thickness of the coating layer is 5~50nm.
4. A method for preparing a positive electrode material as described in any one of claims 1-3, characterized in that, It includes the following steps: Glass additives, lithium fast ion conductor precursors, and lithium manganese iron phosphate powder are mixed and heat-treated to obtain the cathode material.
5. The method for preparing the cathode material according to claim 4, characterized in that, The glass additive comprises the following components in molar percentage: 35%~55% B2O3, 15%~30% Li2O, 5%~15% SiO2, 3%~10% Al2O3, 2%~8% ZrO2, and 1%~5% P2O5.
6. The method for preparing the cathode material according to claim 5, characterized in that, The preparation method of the glass additive is as follows: weigh each component raw material according to the proportion, mix them and melt them at 1000~1250℃ for 1-3 hours, quench, dry and ball mill them to obtain a glass additive with a particle size D50 of 0.3~1.0μm; each component raw material is an oxide, carbonate, nitrate or hydroxide.
7. The method for preparing the cathode material according to claim 4, characterized in that, The lithium fast ion conductor is lithium zirconium phosphate, and the lithium fast ion conductor precursor is a solution or powder containing a lithium source, a zirconium source, and a phosphorus source.
8. The method for preparing the cathode material according to claim 4, characterized in that, The sum of the mass of the glass additive and the lithium fast ion conductor accounts for 0.5% to 4.0% of the mass of lithium manganese iron phosphate.
9. The method for preparing the cathode material according to claim 8, characterized in that, The mass ratio of the glass additive to the lithium fast ion conductor is (1:4) to (4:1).
10. The method for preparing the cathode material according to claim 4, characterized in that, The mixing is performed using wet ball milling or solvent dispersion.
11. The method for preparing the cathode material according to claim 4, characterized in that, The heat treatment is carried out in an inert or weakly reducing atmosphere, with the temperature increased to 600-800°C at a rate of 1-5°C / min and held for 2-8 hours.
12. A positive electrode plate, characterized in that, It comprises the positive electrode material as described in any one of claims 1-3.
13. A lithium battery, characterized in that, It comprises the positive electrode as described in claim 12.
Citation Information
Patent Citations
Lithium ion battery positive electrode material transition metal layered oxide and preparation method thereof, positive electrode material and lithium ion battery
CN120978046A
